Presence of blaPER-1 and blaVEB-1 beta-lactamase genes among isolates of Pseudomonas aeruginosa from South West of Iran - Elham Davodian; Nourkhoda Sadeghifard; Abdolmajid Ghasemian; Samileh Noorbakhsh (Springer, 2019)
Pseudomonas aeruginosa isolates have acquired resistance to antibiotics such as novel beta-lactams. The aim of this study was to investigate the blaPER-1, blaVEB-1, and blaPSE-1 genes among isolates of P. aeruginosa among intensive care unit (ICU) patients. Sixty-five isolates were collected. The antibiotic susceptibility testing and combined disk tests were performed to detect the isolates producing extended spectrum beta-lactamases (ESBLs) among ceftazidime-resistant isolates. Polymerase chain reaction (PCR) amplification of blaPER-1, blaVEB-1, and blaPSE-1 genes was conducted. Ten (15.3%) isolates were ESBL-positive, of which 40% (n = 4) belonged to males and 60% (n = 6) were collected from females. Moreover, two and one isolates harbored blaPER-1 and blaVEB-1 genes, respectively.